Neural Basis of Dispositional Awe - Guan, Fang; Xiang, Yanhui; Chen, Outong; Wang, Weixin; Chen, Jun (Frontiers in Behavioral Neuroscience, 2018)
Awe differs from common positive emotions, triggered by vast stimuli, and characterized by a need for accommodation (NFA). Although studies have revealed the downstream effects of awe experience, little is known about the neural basis of dispositional awe. In the current study, we determined the neural correlation of dispositional awe by using voxel-based morphometry (VBM) in 42 young healthy adults, as measured by the Dispositional Positive Emotion Scale (DPES). Results revealed that the dispositional awe score was negatively associated with the regional gray matter volume (rGMV) in the anterior cingulate cortex (ACC), middle/posterior cingulate cortex (MCC/PCC), and middle temporal gyrus (MTG). These results suggest that individual differences in dispositional awe involve multiple brain regions related to attention, conscious self-regulation, cognitive control, and social emotion. This study is the first to provide evidence for the structural neural basis of individual differences in dispositional awe.